A comparative study of internal organs of silkworm species (Bombyx mori, Samia ricini, Antheraea mylitta, Antheraea assamensis) using stereo-zoom microscopy - Harshitha Prakash; Pawan Shukla; Gangavarapu Subrahmanyam; Himanshu Dubey; Rajal Debnath; K. P. Arunkumar; B. S. Harshitha; Ranjana Gautam; S. Manthira Moorthy (Zoomorphology, 2026)

Study on the Mechanical, Microstructural, and Environmental Assessment of Concrete Containing High Volume Fly Ash and Waste Tyre Steel Fibers - Sankar B; Rameshkumar D; Gautham Kishore Reddy; Arunkumar K; Vishnuprasad V Prabhakar; Anamika S M (Circular Economy and Sustainability, 2026)

Microalgae-Bacteria Interactions in the Bio-based Circular Economy: Mechanisms and Biotechnological Applications - Claris Romy; J. V. Neehara; Maruthanayagam Veerabadhran; Nagaraj Subramani; K. Perumal; K. Arunkumar (Current Microbiology, 2026)

Integrated evaluation of direct-expansion solar-assisted heat pump systems with climate-compatible refrigerants using life cycle impact and cost metrics - Arunkumar Munimathan; K. Senthil Kumar; M. Kannan; Ratchagaraja Dhairiyasamy; Mamdooh Alwetaishi; Ali Keçebaş (Energy and Buildings, 2026)

Climatology of hailstorms over India (1994–2023): exploring trends and associations with thermodynamic indices - Bhavyasree; S. K. Panda; Unashish Mondal; Arunkumar R; Devesh Sharma; Someshwar Das (Natural Hazards, 2026)

Strategic considerations for nutrient use efficiency in sugarcane: Physiological, molecular and genetic perspectives - V. Krishnapriya; R. Manimekalai; R. Gomathi; Van Hay Duong; R. Arunkumar; P.T. Prathima; K. Devakumar; K. Thamilarasi; H.K. Mahadeva Swamy; Amaresh; P. Govindaraj; Prasanta K. Dash (Plant Science, 2026)

Testicular temperature gradient and vascular perfusion as predictors of semen quality in summer-stressed Murrah bulls - Divyanshu Lakhanpal; Tushar Kumar Mohanty; Mukesh Bhakat; Ramaswamy Arunkumar; Rubina K. Baithalu; Anjali Chauhan (Journal of Thermal Biology, 2026)

Innovative black-coated concrete solar still for rural water purification: Regression-optimized thermal performance, water quality, and microbial safety - K. Shanmugasundaram; Arunkumar Selvam; Chih-Yu Kuo; Mani Govindasamy (Journal of Water Process Engineering, 2026)

Multi-trait index based Elucidation of drought tolerance potential of Saccharum spontaneum - T. Lakshmi Pathy; V. Vinu; R. Arunkumar; Gopalareddy Krishnappa; H. K. Mahadeva Swamy; R. Valarmathi; K. Dhanapal; Amaresh; P. Govindaraj; G. Hemaprabha; Bakshi Ram (Plant Physiology Reports, 2025)

Evaluation of stable reference genes for RT-qPCR analysis in Antheraea assamensis (Lepidoptera: Saturniidae) during pathogenic infections - Indumathi Kamatchi Balakrishnan; Himanshu Dubey; Pawan Shukla; Rajal Debnath; C. Vanitha; Gangavarapu Subrahmanyam; Manthira moorthy; Kallare P. Arunkumar; Vikram Kumar; Abhishek Singh; K. M. Ponnuvel (Molecular Biology Reports, 2025)

Testicular thermoregulation and blood perfusion score as markers of sperm quality in summer-stressed breeding bulls - D. Lakhanpal; T. K. Mohanty; M. Bhakat; R. Arunkumar; D. Nain; R. Baithalu (Tropical Animal Health and Production, 2025)

Brown algae biomass valorisation by fucoidan and alginate separation from fucoxanthin extracted residue and shelf-life assessment of one-year stored biomass - K. Anjana; K. Arunkumar (Biomass and Bioenergy, 2025)

Physiological basis and metabolite profiles of pre harvest sprouting resistance in rice varieties of Tamil Nadu - J. Deepika; D. Vijayalakshmi; Santosh Ganapati Patil; S. Vellaikumar; P. Arunkumar; V. Ravichandran; K. Thirukumaran (Cereal Research Communications, 2025)

Exploring water quality in villupuram district: Correlation analysis of physicochemical parameters and health risks for domestic consumption - K. Shanmugasundaram; Arunkumar Selvam; Chih-Yu Kuo; Mani Govindasamy (Journal of Water Process Engineering, 2025)

Biological and genomic characterization of a cypovirus isolated from golden muga silkworm, Antheraea assamensis Helfer (Lepidoptera: Saturniidae) - Iyyangar Deepika; Abhishek Singh; Indira Kumar; Gowtham K; Roja Gnanasekaran; Himanshu Dubey; Rajal Debnath; Pawan Shukla; Kangayam M. Ponnuvel; Vikram Kumar; K.P. Arunkumar; Hanamant Gadad; et al. (Journal of Invertebrate Pathology, 2025)

Microalgal Neutral Lipid Accumulation: Cellular Mechanism and Ways to Improve Biodiesel Production - M. Sreelakshmi; K. Arunkumar (BioEnergy Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Sustainable CaZrO3@CB nanocomposite for sensitive and reliable electrochemical sensing of rutin in complex matrices - Naveenkumar K; M.G. Gopika; Arunkumar Selvam; Youssef Bakkour; Thamraa Alshahrani; Beena Saraswathyamma; Chih-Yu Kuo; Mani Govindasamy (Journal of Environmental Chemical Engineering, 2025)

Effect of age-associated oxidative stress on sperm viability, acrosomal integrity and sperm apoptosis and DNA fragmentation in Sahiwal breeding bulls - Vinod Kumar Gupta; Tushar Kumar Mohanty; Mukesh Bhakat; A. Kumaresan; Rubina K. Baithalu; Nishant Kumar; Raju Kumar Dewry; Dipti Nain; Rishipal Yadav; Ramasamy Arunkumar; Aye Soe (Veterinary Research Communications, 2025)

Exploring potential biological applications of green derived silver nanoparticles using Codiaeum variegatum leaf extract - Arunkumar Lagashetty; M Anusha; Rachana; M Channabasavaraja; Shivakumar; V Veena; R․K Preeti; Sangappa K. Ganiger (Next Research, 2025)

Subcooled flow boiling in a horizontal circular pipe under high heat flux and high mass flux conditions - Deepak K. Solanki; Kausik Nandi; Joe Mohan; Arunkumar Sridharan; S.V. Prabhu (Annals of Nuclear Energy, 2025)

Contrasting gut bacteriomes unveiled between wild Antheraea assamensis Helfer (Lepidoptera: Saturniidae) and domesticated Bombyx mori L. (Lepidoptera: Bombycidae) silkworms - Gangavarapu Subrahmanyam; Yeruva Thirupathaiah; N. Vijay; Rajal Debnath; K. P. Arunkumar; Mallikarjuna Gadwala; Prashant A. Sangannavar; S. Manthira Moorthy; Mahananda Chutia (Molecular Biology Reports, 2024)

A novel dynamic batching energy management strategy for multi-microgrid networks with enhanced privacy - C.P. Albert Paul Arunkumar; K. Selvakumar (Energy and Buildings, 2024)

Greening the oil industry: Microalgae biorefinery for sustainable oil-produced water treatment and resource recovery - Mohammad Sibtain Kadri; Nayana K.; Reda Fassi Fihri; Gholamreza Abdi; Sukumar C.; Arunkumar Kulanthaiyesu (Journal of Water Process Engineering, 2024)

Efficiency of female age of egg parasitoids on parasitism of Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) eggs of various ages - K. Veena; Arunkumar Hosamani; A. Prabhuraj; Shivanand G. Hanchinal; Mallikarjun Kenganal; Sharanabasappa S. Deshmukh (Journal of Plant Diseases and Protection, 2024)

Growth and productivity of Haematococcus pluvialis and Coelastrella saipanensis by photosystem modulation for understanding the heterotrophic nutritional strategy for bioremediation application - K. Nayana; Vaishnav S. Babu; D. Vidya; M.P. Sudhakar; Kulanthaiyesu Arunkumar (Environmental Research, 2024)

(Re)-thinking the red seaweed biomass for biofuel production to meet sustainable development goals toward circular bioeconomy - M. P. Sudhakar; K. Arunkumar; G. Dharani; Thangavel Mathimani (Energy, Ecology and Environment, 2024)

Synthesis and characterization of calcium oxide nano particles obtained from biowaste and its combustion characteristics in a biodiesel operated compression ignition engine - J. Jayaprabakar; A. Karthikeyan; K. Vijai Anand; T. Arunkumar; N. Anbazhaghan; Gayathri Rangasamy (Fuel, 2023)

A rationally designed hetero-assembly of 2D/2D Nitrogen-doped MXene/Graphene via supercritical fluid processing for high energy durable supercapacitors - K. Nasrin; M. Arunkumar; N. Koushik Kumar; V. Sudharshan; S. Rajasekar; D. Mukhilan; M. Arshad; M. Sathish (Chemical Engineering Journal, 2023)

Mitigating abiotic stresses using natural and modified stilbites synergizing with changes in oxidative stress markers in aquaculture - D. Arunkumar; K. K. Krishnani; Neeraj Kumar; B. Sarkar; A. K. Upadhyay; P. B. Sawant; N. K. Chadha; R. Abisha (Environmental Geochemistry and Health, 2023)

Effect of Volume and Surface Area on Growth and Productivity of Microalgae in Culture System - K. Nayana; D. Vidya; K. Soorya; Aswathi Dineshan; Anaswara S. Menon; Rashida Mambad; K. Arunkumar (BioEnergy Research, 2023)

Cytotoxic characterization of optically negative Codium fragile polysaccharide against HeLa and MCF cell lines - Kulanthaiyesu Arunkumar; K. Shreedharan Sreena; Muhsina Moosa; Ganesan Mohan; Rathinam Raja (Bioactive Carbohydrates and Dietary Fibre, 2023)

The impacts of Mn ion incorporation on the structural, optical, and magnetic properties of hematite NPs - S. James Jayaseelan; K. Parasuraman; D. Benny Anburaj; M. Jothibas; B. Arunkumar (Nanotechnology for Environmental Engineering, 2023)

Doppler indices of uterine arteries and mRNA transcripts of hormone receptors in cervix vis-à-vis dilatation therapy in buffaloes affected with incomplete cervical dilatation associated with uterine torsion - Ravjibhai K. Chaudhari; Tarunkumar V. Sutaria; Arunkumar C. Patel; Chandrakant F. Chaudhari (Animal Reproduction Science, 2023)

Characterization of Power Ultrasound Modified Kappaphycus alvarezii Biosorbent and its Modeling by Artificial Neural Networks - Sumit Kumar; S. Nisanth Manokar; Nirmal Thirunavookarasu; V. Nivethitha; T. N. Nidhusri; T. Niranjana; C. K. Sunil; S. Vignesh; Arunkumar Anandharaj; Ashish Rawson (Water, Air, & Soil Pollution, 2022)

Correction to: Evaluating an isotonic aqueous formulation of Chaetomium globosum Kunze for the management of potato black scurf disease caused by Rhizoctonia solani Kuhn in India - Arunkumar K; S. Parthasarathy; S. Harish; Lingan Rajendran; T. Raguchander (Journal of Plant Pathology, 2022)

Evaluating an isotonic aqueous formulation of Chaetomium globosum Kunze for the management of potato black scurf disease caused by Rhizoctonia solani Kuhn in India - Arunkumar K; S. Parthasarathy; S. Harish; Lingan Rajendran; T. Raguchander (Journal of Plant Pathology, 2022)

Development of Improved Strategies for the Survival of Lactobacillus Plantarum MTCC 1407 in Probioticated Custard Apple Juice - M. Arunkumar; S. K. Divya; N. Mahesh; S. Balakumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

1,25(OH)2-vitamin D3 upregulates glucose uptake mediated by SIRT1/IRS1/GLUT4 signaling cascade in C2C12 myotubes - Prasenjit Manna; Arunkumar E. Achari; Sushil K. Jain (Molecular and Cellular Biochemistry, 2018)

Genetic relatedness does not predict the queen’s successors in the primitively eusocial wasp, Ropalidia marginata - Saikat Chakraborty; Shantanu P. Shukla; K. P. Arunkumar; Javaregowda Nagaraju; Raghavendra Gadagkar (Journal of Genetics, 2018)

Phosphorus dynamics and solubilizing microorganisms in acid soils under different land uses of Lesser Himalayas of India - Ranjan Paul; Raj Deo Singh; A. K. Patra; D. R. Biswas; Ranjan Bhattacharyya; K. Arunkumar (Agroforestry Systems, 2017)

Hand, foot and mouth disease (HFMD): emerging epidemiology and the need for a vaccine strategy - S. Aswathyraj; G. Arunkumar; E. K. Alidjinou; D. Hober (Medical Microbiology and Immunology, 2016)

l-Cysteine supplementation increases adiponectin synthesis and secretion, and GLUT4 and glucose utilization by upregulating disulfide bond A-like protein expression mediated by MCP-1 inhibition in 3T3-L1 adipocytes exposed to high glucose - Arunkumar Elumalai Achari; Sushil K. Jain (Molecular and Cellular Biochemistry, 2016)

Antioxidant activity and lipid profile of three seaweeds of Faro, Portugal - Rathinam Raja; Shanmugam Hemaiswarya; K. Arunkumar; Isabel S. Carvalho (Brazilian Journal of Botany, 2016)

Impact of industrial salt effluent and seaweed liquid fertilizers on three microalgae - Rathinam Raja; Shanmugam Hemaiswarya; Isabel S. Carvalho; K. Arunkumar (Brazilian Journal of Botany, 2015)

Release modulation of highly water soluble drug using solid dispersion: impact of dispersion and its compressed unit - Punit B. Parejiya; Bhavesh S. Barot; Hetal K. Patel; Dharmik M. Mehta; Pragna K. Shelat; Arunkumar Shukla (Journal of Pharmaceutical Investigation, 2014)

Effect of melatonin supplementation and cross-fostering on renal glutathione system and development of hypertension in spontaneously hypertensive rats - Lee Siew-Keah; Arunkumar Sundaram; K. N. S. Sirajudeen; Rahimah Zakaria; H. J. Singh (Journal of Physiology and Biochemistry, 2014)

Characterization of mode of reproduction in Commiphora wightii [(Arnot) Bhandari] reveals novel pollen–pistil interaction and occurrence of obligate sexual female plants - K. A. Geetha; Aarti Kawane; Ashok Kumar Bishoyi; Arunkumar Phurailatpam; C. Ankita; S. K. Malik; R. Srinivasan; S. R. Bhat (Trees, 2013)

Identification of sex-specific DNA markers in betel vine (Piper betle L.) - Sanghamitra Samantaray; Arunkumar Phurailatpam; Ashok Kumar Bishoyi; K. A. Geetha; Satyabrata Maiti (Genetic Resources and Crop Evolution, 2012)

Effects of antenatal, postpartum and post-weaning melatonin supplementation on blood pressure and renal antioxidant enzyme activities in spontaneously hypertensive rats - S. K. Lee; K. N. S. Sirajudeen; Arunkumar Sundaram; Rahimah Zakaria; H. J. Singh (Journal of Physiology and Biochemistry, 2011)

Drosophila intersex orthologue in the silkworm, Bombyx mori and related species - K. P. Arunkumar; J. Nagaraju (Genetica, 2011)

Glutathione system in young spontaneously hypertensive rats - S. K. Lee; Sundaram Arunkumar; K. N. S. Sirajudeen; H. J. Singh (Journal of Physiology and Biochemistry, 2010)